(NgRAVDANSTWO (B:s (NsB(B. (NPRAWOWYH DOKUMENTOW (B/s - (NmAZUROW(B, (Na(B. (Nw(B.s ((NmOSKWA (B:s (N`RAJT (B: (N`RAJT(B-(NiZDAT(B,s, 2003)
(NsBORNIK SODERVIT(B: (NKOMMENTARIJ K fz (B"(No GRAVDANSTWE rf(B"; (NWSE O POLU^ENII(B, (NIZMENENII I PREKRA]ENII GRAVDANSTWA(B; (NNORMATIWNYE AKTY mwd rOSSII I mid rOSSII(B. (NdLQ [IROKOGO KRUGA ^ITATELEJ(B.s
Keywords: (NpRAWOs -- (NgRAVDANSTWOs -- (NsBORNIK DOKUMENTOWs -- (NrOSSIJSKAQ fEDERACIQs